Dandy –Walker Malformation with Patent Ductus Arteriosus– A Case Report - Begum, Most Umme Habiba; Rahman, Md Anisur (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Dandy–Walker malformation (DWM) is a group of congenital human brain malformation with specific characteristics. It may be associated with a number of other organ malformation including heart, eye, and thyroid glands. In our case, DWM was associated with heart malformation in the form of patent ductus arteriosus (PDA) and was complicated by atrial fibrillation. The case was established by computed tomography of brain, echocardiography and electrocardiography. The patient was asymptomatic until 7 years of age. J Bangladesh Coll Phys Surg 2018; 36(3): 128-131